Violent to Non-Violent Displacement - Dhian Cahyati‬, Devy (PCD Journal, 2022)
This article discusses land contestation as a factor in the creation of agrarian conflict and the marginalisation of local people. Through field research in Register 45 Mesuji, Lampung, the author explores the geographical displacement of the indigenous people and forest squatters who occupied the land since the fall of The New Order. This paper attempts to explain the strategies used by corporations to displace local people and accelerate capital accumulation. In such situations, the state functions to legitimise the process of land displacement. However, where violence is used for displacement, this indicates a failure to uphold the global norm of human rights. This article shows that the process of displacement has continued through contract farming, i.e., partnership programmes used to control the land in Register 45 and limit squatters' access. In this situation, forest squatters are used as labourers who benefit the company by easing its capital accumulation. However, squatters have rejected this mechanism, preferring to remain independent.